te001217: Politieke karikatuur, Wetgevende verkiezingen 1954
"Zie ook: te001216Zie ook: te001218Zie ook: te001219Zie ook: te001220Zie ook: te001221Zie ook: te001222Zie ook: te001223 FULL TEXT AVAILABLE AT AMSAB-ISH"